Optimalization Of Waqf Management In Indonesia - Ananda Putri Sephiani; Anggraini Diah Hardata Putri; Salsabila Nazhifah; Vandi Verdiansyah; Surya Kusumah; Mohd Koharuddin Bin Mohd Balwi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research is aimed at maximizing public trust in nazhir, through efforts to optimize waqf management. This research takes a qualitative approach, with data obtained through literature studies collected from various scientific articles, journals and other publications that discuss relevant topics. Data analysis was carried out by utilizing SWOT analysis, to find strengths, weaknesses, opportunities and threats in the implementation of waqf management in Indonesia. The research results show that its strength is because the majority of Indonesia's population is Muslim, so its application can be more realistic. Meanwhile, the weaknesses are due to the low level of nazhir transparency, unprofessional waqf management, as well as promotional and development activities of waqf that is not yet optimal. This waqf management has the opportunity to launch a cash waqf type. However, what needs to be paid attention to are threats in the form of a lack of public understanding of the implementation of waqf, the emergence of the danger of waqf nazhir, and various social investments. The researchers formulated several strategies that were considered effective for overcoming waqf management problems, such as through implementing improvements to waqf management, maximizing marketing and promotional activities, and improving nazhir certification.